Effects Of Intradialytic Resistance Trainning On Functional Capacity, Strengh And Body Composition In Hemodialysis Patients - Bruno Bessa; Cristiane Moraes; Amanda Barros; Jorge Barboza; Elirez Silva; Julie Lobo; Denise Mafra (The Korean Society of Nephrology, 2012)
Hemodialysis patients (HD) present inflammation, metabolic acidosis and anorexia which contribute to loss of functional capacity, muscle mass and strength. Resistance training (RT) is recognized to reduce these effects on the musculoskeletal system. This study aimed to evaluate the effects of intradialytic RT on the functional capacity, strength and muscle mass in HD patients. Eighteen HD patients (50% men, 49.3±11.5 years, BMI 22.7±3.9 kg/m2, 63.2±46.3 months on dialysis) exercised 3 times a week for 6 months. All parameters were evaluated before and after 6 months of RT. There were significant changes in the functional tests 10-TSS (10 times Sit-to-Stand Test) and SS-60 (amount of sit to stand in 60 seconds), in the muscle mass and % of body fat after RT. The medial and proximal leg circumferences increased significantly and no differences were observed in torque extensor and flexor and distal leg circumferences. In conclusion, RT contributes to improving body composition and functional capacity of HD patients. Parameters Before RT After RT 10-TSS (seconds) 27.9±6.4 21.9±4.1* SS-60 (repetitions) 26.0±6.7 28.9±5.7* Muscle mass - men (kg) 48.0±9.1 51.5±10* Muscle mass - women (kg) 34.1±4.4 36.9±4.9* Body fat - men (%) 29.2±5.1 25.3±5.1* Body fat - women (%) 34.6±5.1 32.4±4.7* LG- Proximal -R (cm) 53.6±6.6 55.4±6.7* LG- Proximal -L (cm) 52.7±5.8 54.1±6.7 LG- Medial -R (cm) 46.8±5.1 48.6±4.9* LG- Medial -L (cm) 46.6±4.4 48.5±5.4* LG- Leg circumference; R-right; L- left; ⁎ p<0.01.